Parents’ Knowledge and Behavior Related to Pneumonia Incidence in Children Under Five: A Literature Review - Lale Nubya Nitzana; Wayan Sulaksmana Sandhi Parwata; Titi Pambudi Karuniawaty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Pneumonia remains a leading cause of morbidity and mortality among children under five worldwide, including in Indonesia, with its severity influenced by immunization status, air pollution exposure, delayed access to healthcare, and families’ socioeconomic and behavioral conditions.of families influence the severity of pneumonia. This review aims to explore parental knowledge and behavior and the severity of pneumonia in children under five based on previous studies. This study used a literature review method by collecting and analyzing relevant articles from databases such as PubMed, Google Scholar, and ScienceDirect using keywords including